Furthering World Bank Group's Corporate Environmental Sustainability - Kumar, Monika; Rubinfield, Adam; Moore, Judith; Raposa, Sarah; Fyodorova, Maria (World Bank, Washington, DC, 2017)
The World Bank Group (WBG) has focused on reducing the environmental impacts of its internal operations and improving corporate environmental practices since 2002, when the WBG President announced WBG's commitment to Corporate Social Responsibility (CSR). The objective of this document is to summarize the actions WBG has taken thus far to reduce environmental impacts from internal operations and present an action plan to further integrate sustainability into WBG's internal operations. Although this work focuses on the environmental impact associated with WBG daily operations, the links between WBG policies and actions related to environmental management and the financial/social considerations are significant. The International Finance Corporation (IFC) footprint and World Bank corporate responsibility teams facilitate the sustainability commitment of the WBG and monitor and track its progress. These teams provide technical information and research support to a dedicated group of champions throughout the WBG who implement emission reduction activities. Budget for these activities flows primarily through the environment department, the general services department, and IFC facilities management and administration. The environment department and IFC facilities management each resource one staff member to provide back-up research support and to monitor and report on environmental metrics, with building engineers and managers and project officers from across the WBG contributing.